Superalloys 718, 625, 706 and Various Derivatives (1997) 1997
DOI: 10.7449/1997/superalloys_1997_629_637
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Resistance of Alloy 625 Sheet

Abstract: Alloy 625 has been used often in applications which take advantage of its fatigue resistance. The factors which influence fatigue resistance of alloy 625 sheet material at room temperature including composition, cold-work, and grain size have been examined. In particular, the properties of the UNS NO6626 alloy (restricted composition for bellows applications per AMS 5879) will be compared to UNS NO6625 (AMS 5599) and to material produced according to US Patent 4,765,956[11. Data show that UNS NO6626 alloy she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…There has been only limited investigation into the fatigue life, crack propagation, and fracture toughness of additively manufactured alloy 625 [4,28,29]. It was reported that the fatigue life of the cast and additively manufactured parts is significantly lower compared to the wrought material [30]. While this report did not demonstrate the root cause of the lower performance, a different investigation into Ti-6Al-4V [31] demonstrated four key factors for fatigue performance: (1) residual stress, (2) microstructure, (3) porosity, and (4) surface finish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been only limited investigation into the fatigue life, crack propagation, and fracture toughness of additively manufactured alloy 625 [4,28,29]. It was reported that the fatigue life of the cast and additively manufactured parts is significantly lower compared to the wrought material [30]. While this report did not demonstrate the root cause of the lower performance, a different investigation into Ti-6Al-4V [31] demonstrated four key factors for fatigue performance: (1) residual stress, (2) microstructure, (3) porosity, and (4) surface finish.…”
Section: Introductionmentioning
confidence: 99%
“…The fatigue behavior of cast alloy 625 has been summarized in Refs. [4,30]. Despite some investigation into the fusion processes of metallic materials, there is little information on the fatigue behavior of BJ3DP parts made from metallic materials.…”
Section: Introductionmentioning
confidence: 99%